Histological Evidence of Tumour Rejection After Active Immunotherapy in Human Malignant Disease. Issue 5807 (22nd April 1972) - Taylor, Geoffrey; Odili, J. L. I.
Abstract : Active immunotherapy with multiple doses of tumour homogenate incorporated in complete Freund adjuvant was used to treat 12 patients with advanced malignant disease. Evidence of some tumour destruction was observed in 10. Improvement in general clinical condition and the disappearance of symptoms referable to tumour occurred in seven of the patients. The duration of improvement varied considerably. Histological evidence of lymphocytic infiltration, necrosis, and fibrous replacement of tumour tissue is presented.